2015
DOI: 10.1007/978-3-319-19440-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Electro-Mechanical Properties of Interpenetrating Phase Composites with Periodic Architectured Reinforcements

Abstract: In this study, the multifunctional properties (thermal, electric, and mechanical properties) of a new type of three-dimensional (3D) periodic architectured interpenetrating phase composites (IPCs) are investigated computationally. These new IPCs are created using two interconnected, bicontinuous, and intertwined material phases. The inner reinforcing phase takes the shape of the 3D morphology (architecture) of the mathematically-known triply periodic minimal surfaces (TPMS). The TPMS reinforcements are 3D soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…19,20 Most previous studies are mainly limited to the observation of their acoustic/elastic properties. Particularly, with the advanced additive manufacturing (also known as 3D printing) technique, 21 TPMS structures have been utilized in many fields, such as photonic, 22 acoustic, 23 elastic, 24 mechanical, 8 and heat/electrical transport 25 applications. Therefore, further insights into the TPMS structures’ use as acoustic metamaterials are essential.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Most previous studies are mainly limited to the observation of their acoustic/elastic properties. Particularly, with the advanced additive manufacturing (also known as 3D printing) technique, 21 TPMS structures have been utilized in many fields, such as photonic, 22 acoustic, 23 elastic, 24 mechanical, 8 and heat/electrical transport 25 applications. Therefore, further insights into the TPMS structures’ use as acoustic metamaterials are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, researchers have used mathematical equations to produce a different type of TPMS-based unit cell for functional grading and hybridization [32][33][34][35]. Many researchers have determined the mechanical, electrical, and thermal attributes of TPMS-based structures [36][37][38][39][40]. Moreover, Abueidda et al [36,41,42] reported that these structures exhibit better properties as compared to their analog structure due to their better interconnectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike discrete composites reinforced with dispersed (discontinuous) particles or fibers, the exhibited interconnectivity of co‐continuous composites implies that if one phase is eradicated, the remaining phases would still form perpetual, self‐supporting structures. This structural co‐continuity promotes enhanced, thermal, mechanical, and electrical properties …”
Section: Introductionmentioning
confidence: 99%